(untitled) (Książnica Śląska, 2025)
The text restores the memory of the first woman employed in the Silesian Sejm Library in Katowice, and then in the Silesian Public Library from 1931 to 1939. The woman was, completely forgotten, Irena Klonowska-Strzodowa, an extraordinary figure, a muse of poets, and a social and independence activist who paid with her life for the hardships of work in 1945. Although she worked in the library for a relatively short time she co-created its history and is worth recalling in the jubilee year. She was also involved in Upper Silesia’s public life, especially during the uprisings and the plebiscite. From small press notes, a few archival documents and fractions of memories, attempts were made to reconstruct the biography of this first librarian of the Silesian Sejm Library.